The Relevance of Islamic Law and Positive Law in State Safety Management: Literacy Study of Islam and National Law - Hadi, Muhammad (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2022)
In Indonesia, there are several sources of law, including religious law, customary law, international law, state law, and Islamic sharia law. This study aims to obtain scientific evidence about the relevance of Islamic law and state law in managing security and comfort among citizens in Indonesia. We searched for data to answer this problem online in several literature sources, which we discussed comprehensively to answer this research problem by looking for the relationship between Islamic law, state law, and the stability and diversity of citizens. Data collection was carried out online in several literature sources comprehensively to answer research problems, namely looking for the relationship between Islamic law, state law, and the stability and diversity of citizens. This data is sourced from secondary materials, which can be obtained in qualitative measures. The results show that there are eight Islamic laws and state laws to regulate the life of the state and society in a just and prosperous life. Di Indonesia, terdapat beberapa sumber hukum, antara lain hukum agama, hukum adat, hukum internasional, hukum negara, dan hukum syariah Islam. Penelitian ini bertujuan untuk memperoleh bukti ilmiah tentang relevansi hukum Islam dan hukum negara dalam mengelola keamanan dan kenyamanan antar warga negara di Indonesia. Pengambilan data dilakukan secara online di beberapa sumber literatur secara komprehensif untuk menjawab masalah penelitian, yaitu mencari hubungan antara hukum Islam, hukum negara, stabilitas dan keragaman warga negara. Analisis data meliputi interpretasi data, evaluasi, pengkodean data, dan penarikan kesimpulan dengan berpegang pada prinsip validitas dan reliabilitas data. Data ini bersumber dari bahan sekunder, yang dapat diperoleh dalam ukuran kualitatif. Hasil penelitian menunjukkan bahwa ada delapan hukum Islam dan hukum negara untuk mengatur kehidupan bernegara dan bermasyarakat dalam kehidupan yang adil dan makmur